IMPLEMENTASI PENATAUSAHAAN, AKUNTABILITAS PENGELOLAAN DAN PELAPORAN ALOKASI DANA DESA (ADD) DALAM PROSES PEMBANGUNAN DESA KERTAYASA KECAMATAN KRAMAT KABUPATEN TEGAL - Ullum Inti Fahmi; Inayah Adi Sari; Yantie Puji Astutie (Program Studi Magister Manajemen, Universitas Pancasakti Tegal - Indonesia, 2018)
This study aims to determine the implementation of administration, accountability management and reporting the allocation of village funds (ADD) in the process of village development kertayasa kramat district tegal district. To achieve the test, used descriptive method with qualitative approach. Technique of data collection is done by observation, interview and documentation. The result of the research shows that the administration of ADD in Kertayasa Village has been good and according to the procedure, the accountability of ADD management has applied good principle and in accordance with the applicable regulation, the reporting of ADD has applied transparency and accountable principles and is in accordance with the rules set by the central government and Supervision and Development Kertayasa village has done well. Furthermore, in the village of Kertayasa in the making of reporting has been using the system that has been established by the Central Government of Village Finance System (SISKEUDES).Keywords: Village Fund Allocation, Administration,, Management Accountability and Reporting